Central Bank Independence : A Free Lunch? - Debelle, Guy (IMF Working Papers; Working Paper ;, 1996)
This paper extends the analysis of central bank independence to a model in which there is more than one policymaker. It shows that the degree of central bank independence as generally defined in the existing theoretical literature is only one of the influences on macroeconomic performance. The objectives of the fiscal authority, the commitment mechanisms available to the authorities and the nature of the policy game play a key role in determining the inflation rate and output in the economy. Furthermore, the model can be solved for the optimal degree of inflation aversion of the central bank. , a Working Paper and the authors) would welcome any comments on the present text Citations should refer to a Working Paper of the International Monetary Fund, mentioning the authors), and the date of issuance. The views expressed are those of the author(s) and do not necessarily represent those of the Fund.